Determination of One and the Same Person as a Solution to Identity Disharmonies in Population Administration - Gunabila Bin’Arya Dwitatama; Mahdaniyal Hasanah Nuriyyatiningrum (Universitas KH. Abdul Chalim Mojokerto, 2026)
Identity inconsistencies in population administration are legal issues that impact legal certainty and the fulfillment of citizens' civil rights. Differences in the spelling of identities in official documents often hinder the implementation of legal actions, particularly in the administration of land rights. This study aims to analyze the legal considerations of judges in determining